2022
DOI: 10.3390/land11091459
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Difference Analysis and Impact Factors of Water Ecological Civilization Level: Evidence from Jiangxi Province, China

Abstract: The water environment quality is not high, the spatial and temporal distribution of water resources is uneven, and the water quality-induced water is in shortage in the world. Strengthening the construction of water ecological civilization is one of the important measures to solve these problems. We took China’s Jiangxi Province and its prefecture-level cities as the research object, the water ecological civilization level was measured from the two dimensions of time and space by principal component analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
1
7
1
Order By: Relevance
“…Moreover, the regression results of the impact of technological innovation, import and export trade, and foreign capital on water pollution intensity are similar to those reported Yu and Fang et al on the impact factors of environmental pollution [19,30]. The regression results of the impact of urbanization level on water pollution intensity are similar to those reported by Darko et al, Kan et al and Margaret et al on the relationship between urbanization and ecological environment, who found that the effects of urbanization, such as population upsurge, increased industrialization, urban agriculture, and rural-urban migration of persons, exert pressure on the limited water resources in most cities; the urbanization process not only intensifies the emission of water environmental pollution but also improves the water pollution intensity [60][61][62], although these results are inconsistent with the those reported by Al-Mulali et al, Irfan and Shawon, and Kan et al on the relationship between urbanization and ecological environment, who reported an inverted U curve between urbanization level and the overall quality of the water ecological environment [63][64][65].…”
Section: Estimation Resultsmentioning
confidence: 88%
“…Moreover, the regression results of the impact of technological innovation, import and export trade, and foreign capital on water pollution intensity are similar to those reported Yu and Fang et al on the impact factors of environmental pollution [19,30]. The regression results of the impact of urbanization level on water pollution intensity are similar to those reported by Darko et al, Kan et al and Margaret et al on the relationship between urbanization and ecological environment, who found that the effects of urbanization, such as population upsurge, increased industrialization, urban agriculture, and rural-urban migration of persons, exert pressure on the limited water resources in most cities; the urbanization process not only intensifies the emission of water environmental pollution but also improves the water pollution intensity [60][61][62], although these results are inconsistent with the those reported by Al-Mulali et al, Irfan and Shawon, and Kan et al on the relationship between urbanization and ecological environment, who reported an inverted U curve between urbanization level and the overall quality of the water ecological environment [63][64][65].…”
Section: Estimation Resultsmentioning
confidence: 88%
“…A universal urban water ecological health index was established to evaluate cities from different countries. The scores of water health of the study cities were measured by principal component analysis, due to its advantages of reducing the workload of index selection [54], with a higher score indicating better water ecological construction. To understand how to promote the best urban ecological development model, policy and technical guidance documents were analyzed for the three top-scoring cities to compare each city's water ecological management construction system.…”
Section: Methodsmentioning
confidence: 99%
“…Under the guidance of the concept of water ecological civilization, the health level of urban water ecosystems is mainly the evolution of the interaction between the water system and the human system [29,54,55]. The optimization of various water-related activities is the foundation; at the same time, there is the aim to realize the sustainable supply of aquatic ecosystem services.…”
Section: Development Of the Urban Water Ecosystem Health Evaluation I...mentioning
confidence: 99%
“…Scholars have constructed different index systems using the entropy method, principal component analysis method, analytic hierarchy process, and fuzzy comprehensive evaluation method to measure the WEC situation in different regions of China. These regions include provinces, the Yangtze River Economic Belt, the Yellow River basin, pilot cities of WEC, urban agglomerations, provincial capital cities, and prefecturelevel cities [13][14][15][16][17][18][19][20][21][22]. Most studies show that since the implementation of the WEC pilot policy, the WEC is increasingly improving, and the efficiency of water resource utilization and the quality of the water environment have been significantly improved in pilot cities.…”
Section: Literature Reviewmentioning
confidence: 99%